Team Empowerment Practices - Baillargeat, Camille; Pauknerová, Daniela, 1970-; Schmitt, Judith; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This thesis investigates team empowerment practices employed by leaders in a leading aerospace company. Utilizing a qualitative research methodology, the study conducts in-depth interviews with ten leaders within the organization. The key findings reveal that contemporary leadership approaches emphasize a coaching role over that of a traditional, dominant figure. By providing a clear vision and objectives, leaders foster an environment promoting open communication, trust-building among team members, and the encouragement of innovative thinking. However, the research also identifies challenges associated with empowering teams in the highly regulated aerospace industry. These challenges include time constraints, large team sizes, complex processes, and resistance to change. The findings suggest that the company itself plays a critical role in empowering its employees, with variations in leadership practices and outcomes attributable to industry-specific factors. The study highlights the need for both leaders and organizations to collaborate in overcoming these challenges, thus creating a supportive environment that enables team empowerment and drives overall success.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses